Regional Novels and the Czech Ruralism - Engelbrecht, Wilken (Werkwinkel, 2014)
In the netherlands regional novels have never been considered as real literary works. in Flanders regional literature had a better status, especially because several writers of the Van Nu en Straks movement such as Stijn Streuvels wrote about regional themes. in Czech literature since 1848 regional themes was viewed as important in novels and stories, mainly till the end of world war ii. in 1932 the Catholic writer Antonín Matula defined the so-called ruralism, which became a movement of mainly Catholic writers from the countryside. Most of them were severely persecuted in a constructed Stalinist show trial against the green international in 1951. in his work Hlasy země v evropských literaturách (The Voice of Earth in European Literatures, 1933) Matula discussed nearly all major european literatures, i.e. Flemish regional writers. it is no coincidence that especially Flemish writers such as ernest Claes, Stijn Streuvels and Felix timmermans, were translated into Czech during the second quarter of the 20th century.